(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
An efficient protocol was established for in vitro mass propagation of a valuable medicinal shrubby plant, Mimosa pudica Linn., from shoot tip and nodal explants. Optimum in vitro shoot induction was observed from nodal explants on MS basal medium supplemented with 1.5 mg/l BAP + 0.5 mg/l NAA, in which 88.2% of the explants produced 9 shoots per culture within 3-4 weeks. Repeated subcultures in the same medium, resulted rapid shoot multiplication with 20.4 ± 1.20 shoots per culture within 12 weeks. The healthy in vitro raised shoots rooted on half strength MS medium with 0.5 mg/l IBA. For acclimatization and transplantation, the plantlets in the rooting culture tubes were kept in normal room temperature for 7 days before transplanting in pots where plantlets were reared for three weeks. The survival rate of regenerated plantlets was 80%. Key words: Mimosa pudica; Medicinal plant; Shoot proliferation; In vitro mass propagation; Acclimatization DOI: 10.3329/bjsir.v45i2.5704 Bangladesh J. Sci. Ind. Res. 45(2), 95-100, 2010